1975
DOI: 10.17161/str.1808.6098
|View full text |Cite
|
Sign up to set email alerts
|

Information control in conversations: Honesty is not always the best policy

Abstract: This exploratory research in the sociology of talk is focused on three questions for analysis: (1) One hundred and thirty (130) dyadic encounters were recorded and analyzed; the "actor" is the respondent and the "other" is the person with whom actor has the conversation. An analysis of these encounters revealed that nearly two-thirds of the 870 instances of verbal communications were talk which controlled information. Frequency tables and typologies delineate (1) forms of information control and (2) reasons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 4 publications
2
101
0
3
Order By: Relevance
“…For instance, DePaulo et al (1996) claim that people tell an average of one or two lies daily. Turner et al (1975) found that people lie in about two-thirds of their conversations. In addition, people perceive lies when none actually have occurred (Elaad, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, DePaulo et al (1996) claim that people tell an average of one or two lies daily. Turner et al (1975) found that people lie in about two-thirds of their conversations. In addition, people perceive lies when none actually have occurred (Elaad, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are various forms of deceptions. While Turner et al (1975) categorize deception into lies, exaggerations, half-truths, secrets, and diversionary responses, Utz (2005) takes another approach in computer-mediated communication and categorizes deception into category deception (gender switching), attractiveness deception, or identity concealment. Since true identity of social media users may not be known, it is possible that innocent people may be deceived or abused through misbehavior of deceptive users.…”
Section: Fake Identity and Messaging Schemementioning
confidence: 99%
“…Individuals may respond to criticism in a number of ways, which are considered in the next component of the framework. Equivocation, the use of ambiguity or vagueness as a way to save face in response to a difficult or awkward situation, is one potential response to criticism (Bello & Edwards, 2005;Turner, Edgley, & Olmstead, 1975).…”
Section: Criticism 10mentioning
confidence: 99%